Творчі здобутки дослідника - Данилюк, А. (Народна творчість та етнографія, 2005)
The article commemorates folklore and ethnography work of the great researcher Oleksa Oshurkevych. Biographic facts and a detailed study of the scholar's activities are presented, among which are researches on the Kosach family, traditional folk musical instruments, regional ethnography, etc.